A review of environmental hazards and vertebrate biodiversity of upper San Marcos river, Texas, USA - Safi, Amtyaz; Usman Ali Hashmi, Muhammad (SPC Journal of Environmental Sciences, 2021)
The San Marcos River arises in a series of springs in Hays County, Texas. This is the second largest and important spring system in Texas, which has more environmental stability and a diverse known biotic diversity of any other ecosystems in the southwestern United States of America. The upper San Marcos River contains a relatively larger number of protected biota, including the vertebrate fauna like San Marcos salamander (Eurycea nana) and the fountain darter (Etheostoma fonticola). Many environmental hazards are increasing day by day due to humanâ€™s development and groundwater extraction. This area receives a great deal of conservation efforts to protect/ enhance habitats, protect biodiversity and ecological condition of the river but still much more priority actions are needed.Â Â